Exosomes multifunctional roles in HIV-1: insight into the immune regulation, vaccine development and current progress in delivery system - Habib, Arslan; Liang, Yulai; Zhu, Naishuo (Frontiers in Immunology, 2023)
Human Immunodeficiency Virus (HIV-1) is known to establish a persistent latent infection. The use of combination antiretroviral therapy (cART) can effectively reduce the viral load, but the treatment can be costly and may lead to the development of drug resistance and life-shortening side effects. It is important to develop an ideal and safer in vivo target therapy that will effectively block viral replication and expression in the body. Exosomes have recently emerged as a promising drug delivery vehicle due to their low immunogenicity, nanoscale size (30-150nm), high biocompatibility, and stability in the targeted area. Exosomes, which are genetically produced by different types of cells such as dendritic cells, neurons, T and B cells, epithelial cells, tumor cells, and mast cells, are designed for efficient delivery to targeted cells. In this article, we review and highlight recent developments in the strategy and application of exosome-based HIV-1 vaccines. We also discuss the use of exosome-based antigen delivery systems in vaccine development. HIV-1 antigen can be loaded into exosomes, and this modified cargo can be delivered to target cells or tissues through different loading approaches. This review also discusses the immunological prospects of exosomes and their role as biomarkers in disease progression. However, there are significant administrative and technological obstacles that need to be overcome to fully harness the potential of exosome drug delivery systems.